2023
DOI: 10.1007/s00405-023-08168-6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational variation in incidence of oropharyngeal cancer in the Nordic countries

Abstract: Purpose Evaluate the occupational variation in incidence of oropharyngeal cancer (OPC). Methods We calculated standardized incidence ratios (SIRs) of OPC in occupational categories in the Nordic countries relative to the entire national populations. The data covered 6155 OPC cases. Results Among men high risk of OPC was observed, among else, in waiters (SIR 6.28, 95% CI 4.68–8.26), beverage workers (SIR 3.00, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Notwithstanding the absence of clearly defined associations between occupational exposures and OPC, there are indications suggesting an increased risk in a few professional groups, such as waiters, cooks and stewards, artistic workers, poultry, meat, and soup manufacturing workers, mechanics, construction industry workers, and WTC responders exposed to dust after the September 11 attacks [5,27,[29][30][31]34]. The increased incidence of OPC in waiters may be due to exposure to environmental tobacco smoking, i.e., passive smoking, which in conjunction with their own smoking habits and alcohol consumption might explain the six-fold risk of OPC in this occupational group [14,51]. Exposure to cooking fumes may also have contributed to the excess risk of OPC observed, not only in male cooks and stewards but also in waiters and waitresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding the absence of clearly defined associations between occupational exposures and OPC, there are indications suggesting an increased risk in a few professional groups, such as waiters, cooks and stewards, artistic workers, poultry, meat, and soup manufacturing workers, mechanics, construction industry workers, and WTC responders exposed to dust after the September 11 attacks [5,27,[29][30][31]34]. The increased incidence of OPC in waiters may be due to exposure to environmental tobacco smoking, i.e., passive smoking, which in conjunction with their own smoking habits and alcohol consumption might explain the six-fold risk of OPC in this occupational group [14,51]. Exposure to cooking fumes may also have contributed to the excess risk of OPC observed, not only in male cooks and stewards but also in waiters and waitresses.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Nikkilä et al [14] revealed a high excess risk of OPC among Nordic male artistic workers (SIR = 2.97, 95% CI: 2.31-3.76), seamen (SIR = 2.30, 95% CI: 1.91-2.77), and journalists (SIR = 2.09, 95% CI: 1.33-3.14). Among Nordic women, a statistically significant excess risk of OPC was observed in packers, loaders, and warehouse workers (SIR = 1.73, 95% CI: 1.07-2.64).…”
Section: Other Occupational Categoriesmentioning
confidence: 98%
See 1 more Smart Citation